A Systematic Literature Review on The Effectiveness of The Teams Games Tournament (TGT) Model with Flashcard Media in Enhancing Early Reading Skills in Elementary School Students - Anggraeni, Devi; Supriatna, Encep; Sopandi, Wahyu (International Conference on Elementary Education, 2025)
Early reading ability is a fundamental literacy skill that underpins students’ success in subsequent learning stages. However, numerous studies indicate that many elementary school students still struggle with early reading, particularly in letter recognition, syllable decoding, and basic comprehension. One promising approach to address this issue is the integration of the Teams Games Tournament (TGT) learning model with flashcard media. This study aims to systematically review research findings on the effectiveness of the TGT model assisted by flashcards in improving early reading skills among elementary school students. The study employed a Systematic Literature Review (SLR) method following the PRISMA guidelines, analyzing articles published between 2014 and 2025 from databases such as Google Scholar, ERIC, and ScienceDirect. From an initial pool of 134 articles, 25 met the inclusion criteria and were further analyzed. The findings reveal that the integration of the TGT model and flashcard media effectively enhances students’ learning motivation, engagement, and early reading proficiency, particularly in letter and word recognition. Most studies employed quasi-experimental designs using pretest-posttest methods. Thematic analysis identified four major research focuses: (1) the effectiveness of the TGT model on reading outcomes, (2) the pedagogical role of flashcards in interactive learning, (3) implementation strategies of TGT in lower-grade classrooms, and (4) challenges faced by teachers in game-based learning application. The review also highlights several research gaps, including intervention duration, school context diversity, and long-term retention measurement. This SLR provides valuable insights for educators and researchers in designing innovative and effective instructional models to improve early reading skills in elementary education.